2020
DOI: 10.5056/jnm19188
|View full text |Cite
|
Sign up to set email alerts
|

Anti-reflux Surgery Versus Proton Pump Inhibitors for Severe Gastroesophageal Reflux Disease: A Cost-Effectiveness Study in Korea

Abstract: Background/Aims The economic burden for gastroesophageal reflux disease (GERD) has recently increased in Asian countries. This study investigates the cost-effectiveness between anti-reflux surgery and medication, with proton pump inhibitors (PPIs) for GERD in Korea. Methods We used a decision tree and Markov model to obtain the costs and quality-adjusted life years (QALYs) of the surgical and medical strategies. Our target cohort was the severe GERD patients aged 50 years old who required a continuous double d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…[250][251][252][253][254][255][256][257][258][259] Also, several studies demonstrated that anti-reflux surgery was likely to be cost-effective compared to medical treatment. 255,257,260 From the Statement 22: Anti-reflux surgery can be recommended as an alternative to proton pump inhibitor maintenance therapy to improve symptoms and quality of life in patients with proven gastroesophageal reflux disease.…”
Section: Anti-reflux Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…[250][251][252][253][254][255][256][257][258][259] Also, several studies demonstrated that anti-reflux surgery was likely to be cost-effective compared to medical treatment. 255,257,260 From the Statement 22: Anti-reflux surgery can be recommended as an alternative to proton pump inhibitor maintenance therapy to improve symptoms and quality of life in patients with proven gastroesophageal reflux disease.…”
Section: Anti-reflux Surgerymentioning
confidence: 99%
“…256 Recently, a Korean cost-effectiveness study reported that the anti-reflux surgery was less expensive and more effective therapy over the PPI pharmacotherapy after 9 years of follow-up. 260 Physiological tests, such as a 24hour esophageal pH study, should be performed to prove GERD before surgery, and other esophageal motility disorders should be excluded by conducting esophageal manometry. Anti-reflux surgery is an excellent treatment option with a better long-term effect and cost-effectiveness compared to the PPI therapy.…”
Section: Anti-reflux Surgerymentioning
confidence: 99%
“…Inpatient and day case hospital costs are calculated using detailed bottom-up methods and there are plans to expand activity-based funding to acute outpatient services 2 . Several Irish costing studies have used the casemix costs published by the HPO (e.g., Butler et al, 2016;Connolly et al, 2015;O'Sullivan et al, 2016).…”
Section: Why Unit Costs For Non-acute Care In Ireland?mentioning
confidence: 99%
“…GERD is conventionally treated with medications, such as PPIs and antacids and more recently, anti-reflux surgery has been suggested 11 . However, GERD is still regarded as a highly prevalent and frequently recurrent and refractory disorder.…”
mentioning
confidence: 99%